2019
DOI: 10.1111/acps.13129
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐regression of the impact of policy on the efficacy of individual placement and support

Abstract: Objective Individual placement and support (IPS) has shown consistently better outcomes on competitive employment for patients with severe mental illness than traditional vocational rehabilitation. The evidence for efficacy originates from few countries, and generalization to different countries has been questioned. This has delayed implementation of IPS and led to requests for country‐specific RCTs. This meta‐analysis examines if evidence for IPS efficacy can be generalized between rather different countries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 69 publications
0
83
1
4
Order By: Relevance
“…Over the last decade, a number of systematic reviews and meta-analyses have confirmed this basic finding 4,5 . One metaanalysis reported moderate to large effects favoring IPS for a range of other employment outcomes 5 .…”
Section: An Update On Individual Placement and Supportmentioning
confidence: 85%
See 1 more Smart Citation
“…Over the last decade, a number of systematic reviews and meta-analyses have confirmed this basic finding 4,5 . One metaanalysis reported moderate to large effects favoring IPS for a range of other employment outcomes 5 .…”
Section: An Update On Individual Placement and Supportmentioning
confidence: 85%
“…Rapid expansion of IPS across the world 8 includes at least 19 high-income countries outside the US over the past 20 years (Australia, Belgium, Canada, China, Czech Republic, Denmark, France, Germany, Iceland, Ireland, Italy, Japan, New Zealand, the Netherlands, Norway, Spain, Sweden, Switzerland, and the UK). The flexibility and adaptability of the IPS model facilitate successful adoption with high fidelity and good employment outcomes in countries with diverse sociocultural conditions, labor laws, welfare systems, and economic conditions 4 .…”
Section: An Update On Individual Placement and Supportmentioning
confidence: 99%
“…It is a client-driven model, delivered by a vocational specialist, that allows for ongoing personalised support, even after a suitable placement has been obtained. IPS has consistently proved more effective than other employment services in randomised controlled trials (RCTs) in countries with varying labour markets, economic conditions and attitudes towards mental health [32,[36][37][38][39][40][41][42]. IPS, inclusive of educational support, has been implemented successfully in young people experiencing first-episode psychosis [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…IPS programs obtaining high scores on this scale, as measured by evaluators, obtain higher shares of employment in ordinary jobs [8][9][10]. Through several experimental studies, the IPS method has proved more effective than traditional employment services, providing a robust empirical base for implementation across a wide variety of cultural contexts [11].…”
Section: Introductionmentioning
confidence: 99%